Analisis Faktor Yang Mempengaruhi Mahasiswa Dalam Pemilihan Model Jilbab (Studi Pada Mahasiswi Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Universitas Airlangga) - Ajeng Shelyta; Fatin Fadhilah Hasib (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research aims at determining the factor that influences on selecting the model of their headcovers, it is merely because the model of headcovers worn by the female students are now vary. Therefore, there should be some factors that urges a female student as a consumer to do a reasoned action on selecting the model of headcovers. This research is a quantitative research by using factor explanatory analysis. The characteristic of the population is the students of Islamic Economy, FEB, Airlanga University which are wearing headcovers. The result of this research shows that from 18 factors gained from the data collection which then processed by factor analysis. The researcher found that there are 5 factors, i.e. Want to Show Identitiy, consumers’ environment, consumers’ comfort in dressing up, consumers’ society, and consumers’ ease in dressing up.